Բ. Բլումի տաքսոնոմիան՝ որպես քննադատական մտածողության զարգացման տեխնոլոգիա - Ն. Դ. Դավոյան (ՀՀ ԳԱԱ հրատ.)
Согласно теории Блума, навыки критического мышления в основном приобретаются на уровне анализа, синтеза и оценивания. Выделение данных уровней представляется эффективным особенно при отборе и составлении заданий и упражнений. According to Bloom’s theory of critical thinking skills mostly are acquired at the level of analysis, synthesis and evaluation. To single out these levels can be effective especially in the process of selecting and creating tasks and exercises.
Keywords: L Education